Identification of water-infiltration-induced electrical energy generation by ionovoltaic effect in porous CuO nanowire films. Issue 10 (10th September 2020) - Jin, Huding; Yoon, Sun Geun; Lee, Won Hyung; Cho, Yong Hyun; Han, Junghyup; Park, Junwoo; Kim, Youn Sang
Abstract : We verified the origin of water-infiltration-induced electricity generation by an ionovoltaic effect, specifically, ion–surface interaction induced potential asymmetry in a porous CuO nanowire film. Abstract : We verified the origin of water-infiltration-induced electricity generation by an ionovoltaic effect, specifically, ion–surface interaction induced potential asymmetry in porous structures. When 20 μl of water (NaCl, 0.1 M) infiltrates into a porous CuO nanowire film, electrical power of ∼0.45 V and ∼0.23 μA is produced for 40 minutes. Moreover, a method of proportionally amplifying electricity is presented, and the practicability is shown by turning on an LED with infiltration of eight seawater droplets.